Alcohol Consumption and Longitudinal Trajectories of Physical Functioning in Central and Eastern Europe: A 10-Year Follow-up of HAPIEE Study - Hu, Yaoyue; Pikhart, Hynek; Kubinova, Ruzena; Malyutina, Sofia; Pajak, Andrzej; Besala, Agnieszka; Bell, Steven; Peasey, Anne; Marmot, Michael; Bobak, Martin (The journals of gerontology. Series A, Biological sciences and medical sciences, 2016)
BACKGROUND: Physical functioning (PF) is an essential domain of older persons' health and quality of life. Health behaviors are the main modifiable determinants of PF. Cross-sectionally, alcohol consumption appears to be linked to better PF, but longitudinal evidence is mixed and very little is known about alcohol consumption and longitudinal PF trajectories. METHODS: We conducted longitudinal analyses of 28,783 men and women aged 45-69 years from Novosibirsk (Russia), Krakow (Poland), and seven towns of the Czech Republic. At baseline, alcohol consumption was measured by a graduated frequency questionnaire and problem drinking was evaluated using the CAGE questionnaire. PF was assessed using the Physical Functioning Subscale of the SF-36 instrument at baseline and three subsequent occasions. Growth curve modeling was used to estimate the associations between alcohol consumption and PF trajectories over 10-year follow-up. RESULTS: PF scores declined during follow-up in all three cohorts. Faster decline in PF over time was found in Russian female frequent drinkers, Polish female moderate drinkers, and Polish male regular heavy drinkers, in comparison with regular and/or light-to-moderate drinkers. Nondrinking was associated with a faster decline compared with light drinking only in Russian men. Problem drinking and past drinking were not related to the decline rate of PF. CONCLUSIONS: This large longitudinal study in Central and Eastern European populations with relatively high alcohol intake does not strongly support the existence of a protective effect of alcohol on PF trajectories; if anything, it suggests that alcohol consumption is associated with greater deterioration in PF over time.
Keywords: Alcohol Drinking; Poland; Russia; Central and Eastern Europe; pití alkoholu; Humans; Risk Assessment; následné studie; Czech Republic; Follow-Up Studies; Risk Factors; Surveys and Questionnaires; mužské pohlaví; Česká republika; Physical Fitness; Polsko; Longitudinal Studies; průzkumy a dotazníky; rizikové faktory; Rusko; Alcohol consumption; ženské pohlaví; hodnocení rizik; Physical functioning trajectories; lidé; Aged; Quality of Life; senioři; longitudinální studie; tělesná výkonnost; Male; kvalita života; Female